THE IMPLEMENTATION OF EDUCATION FINANCING THROUGH BOS FUND MANAGEMENT IN IMPROVING EDUCATION QUALITY - Herman, Maman; Mulya, Citra; Apriyanto, Sigit (Universitas Islam Negeri Alauddin Makassar, 2021)
The purpose of this study is to analyze and describe: 1) Implementation of education financing through the management of BOS funds in improving the quality of education; 2) Barriers to the implementation of education financing through the management of BOS funds in improving the quality of education. 3) Efforts made to overcome obstacles in implementing education financing through the management of BOS funds in improving the quality of education. The research method used in the preparation of this scientific paper is descriptive with a qualitative approach. The data collection technique is done through interviews, observation, and documentation study. The informants in this study were the principal, teachers, staff, and other stakeholders in SMA Negeri 1 Kadipaten. The results showed that 1) Implementation of Education Financing through BOS Funds at SMAN 1 Kadipaten Majalengka Regency was effective. This can be seen from several aspects as follows: 1) Planning for Education Budget Compilation is carried out carefully; 2) The education financing is carried out by the operational guidelines and technical guidelines for BOS, and 3) Budget supervision is carried out effectively; 2) There were various obstacles faced in the management of BOS funds in improving the quality of education 3) There were various efforts made to overcome the obstacles faced in implementing the management of education financing through BOS funds in improving the quality of education.